A Post-Marketing Surveillance Study to Evaluate the Safety Profile of AlvotereⓇ (Docetaxel) in Iranian Patients Diagnosed with Different Types of Cancers Receiving Chemotherapy - Farhad Shahi, Associate Professor; Farahnaz Vafaeezadeh, Post doctoral fellowship; Nafiseh Ansarinejad, Associate Professor; Alireza Ahmadi, Post doctoral fellowship; Ali Shahriari-Ahmadi, Associate Professor; Alireza Ghazizadeh, Associate Professor; Hassanali Vahedian Ardakani, Associate Professor; Mohammad Reza Ravanbod, Associate Professor; Sharareh Seifi, Associate Professor; Mohammad Foratyazdi, Associate Professor; Seyed Asadollah Mousavi, Associate Professor; Mansour Rajabi Vahid, Associate Professor; et al. (Elsevier, 2022)
ABSTRACT: Background: Docetaxel is a clinically well established antimitotic chemotherapy medication. Labeled docetaxel indications are breast cancer, gastric cancer, head and neck cancer, non-small cell lung cancer, and prostate cancer. Objective: This is a Phase IV study to evaluate the safety profile of docetaxel (Alvotere; NanoAlvand, Iran) in Iranian patients diagnosed with different types of cancers receiving chemotherapy regimens with docetaxel. Methods: Patients who received Alvotere as a part of their chemotherapy regimen were enrolled in this Phase IV, observational, multicenter, open-label study. Alvotere was administrated as a single agent or in combination with other chemotherapy agents. Safety parameters in each cycle were assessed, and the related data were recorded in booklets. Findings: A total of 411 patients with different types of cancers were enrolled from 25 centers in Iran. The most common malignancies among participants were breast cancer (49.88%), followed by gastric cancer (22.63%). Participants' mean age was 53.33 years, and the mean total dose used in each cycle was 132 mg. According to the results, 341 patients experienced at least 1 adverse event, that the most common was alopecia (41.12%). In total, 92 (22.38%) patients had at least 1 adverse event of grade 3 or 4, and 25 (6.08%) patients showed 54 serious adverse events, which the causality assessment for all was possibly related to Alvotere. There was a significant difference between men and women in the incidence of skin and subcutaneous tissue disorders (55.63% in women vs 41.73% in men; P = 0.009). Also, the incidence of gastrointestinal disorders, nervous system disorders, skin and subcutaneous tissue disorders, hepatic enzymes increase, and fluid retention was significantly higher (P < 0.05) in patients receiving anthracyclines in their chemotherapy regimens. Conclusions: The findings of this open-label, observational, multicenter, postmarketing surveillance showed that Alvotere appears to have an acceptable safety profile in Iranian cancer patients receiving chemotherapeutic regimens. (Curr Ther Res Clin Exp. 2022; 82:XXX-XXX) © 2022 Elsevier HS Journals, Inc.